Pengaruh Nilai Tukar, Jumlah Uang Beredar, dan Tingkat Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia - Nacita Putri Anzelia (Universitas Mercu Buana, 2021)
A country's economy can be viewed from economic growth to public and monetary growth. This article discusses the impact of the Indonesian exchange rate, money supply and inflation. The study argues that three financial factors affect Indonesia's economic growth, which are expressed in gross domestic product (GDP). The data used in this study are secondary data in time series data format for the period 1989-2019. This study uses a variety of regression analysis tools, often using least squares (OLS) and classical hypothesis testing. The results show that the exchange rate and money supply have a significant positive impact on economic growth. Inflation has a significant negative impact on economic growth. It is hoped that this study can be used as an important consideration for the government and the Bank of Indonesia in determining better monetary policy in relation to the development of Indonesian economic growth.